The view of the physical education teacher on the inclusion of students with disabilities in schools of the municipal education network of Rio de Janeiro - Oliveira , Alexandre Dykerman; Santos, Roberto Ferreira dos; Telles, Silvio de Cassio Costa; Copolillo, Marta Lenora; Osborne, Renata (Seven Editora, 2023)
Inclusion is a theme that has been gaining importance in recent decades, especially when we refer to people with disabilities who have been stigmatized and suffered prejudice throughout history. This data serves to ratify that there is an ongoing inclusion process, demanding from schools an ability to organize themselves to receive these students. The present study has as general objective to investigate how the process of inclusion of students with disabilities occurs in schools of the municipal education network of Rio de Janeiro under the perspective of the Physical Education teacher. We used the qualitative approach, which studies subjective aspects of social phenomena and human behavior in specific groups, providing the creation of new approaches, review and elaboration of new concepts and categories during the investigation. For data collection, an observation script was used, a semi-structured guided interview, which was supported by an interview script. Participated in the research 12 Physical Education teachers who work in regular classes of 4 municipal schools in Rio de Janeiro, within the scope of the 2nd CRE (Coordination of Education). We use the Yin cycle in data analysis. We conclude that teachers aspire to training with a more inclusive approach, in addition to regular continuing education. We also highlight the importance of improving the school’s infrastructure and the provision of specific material to better meet the specificities of students. Flexible planning and the offer of diverse activities that minimize competition and favor cooperation were also cited as strategies and gained strength in the teachers’ discourse. Inclusion is everyone’s responsibility, not limited to the teacher, mediator of the process. In the case of Physical Education we highlight the need for a special look at the specificity of the environment, which is based on emotions and movements. DOI:https://doi.org/10.56238/ptoketheeducati-038